Pathophysiologic Role of Neurotransmitters in Digestive Diseases - Yang, Xiaoxu; Lou, Jun; Shan, Weixi; Ding, Jianhong; Jin, Zhe; Hu, Yanxia; Du, Qian; Liao, Qiushi; Xie, Rui; Xu, Jingyu (Frontiers in Physiology, 2021)
Neurotransmitters are special molecules that serve as messengers in chemical synapses between neurons, cells, or receptors, including catecholamines, serotonin, dopamine, and other neurotransmitters, which play an important role in both human physiology and pathology. Compelling evidence has indicated that neurotransmitters have an im-portant physiological role in various digestive diseases. They act as ligands in combina-tion with central or peripheral receptors, and transmits signals through chemical synap-ses, which are involved in regulating the physiological and pathological processes of the digestive tract organs. For instance, neurotransmitters regulate blood circulation and af-fect intestinal movement, nutrient absorption, the gastrointestinal innate immune system, and the microbiome. In this review, we will focus on the role of neurotransmitters in the pathogenesis of digestive tract diseases to provide novel therapeutic targets for new drug development in digestive diseases.